2020
DOI: 10.1093/ehjci/ehaa946.2078
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity troponin I in hypertrophic cardiomyopathy

Abstract: Background ESC guidelines recommend measurement of troponin T in patients with hypertrophic cardiomyopathy (HCM) because high concentrations are associated with cardiovascular events, heart failure and death. The cardiac Troponin I subunit is not expressed in skeletal muscle making it a cardio-specific isoform. The use of troponin biomarkers in management of patients HCM is limited because concentrations only weakly correlate with clinical parameters. Most studies are small, and few have exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In addition, several studies have demonstrated elevated serum levels of cTnI in LGE-positive HCM patients compared to LGE-negative patients [ 6 , 8 , 11 , 17 ]. Besides the mere presence of LGE, some have found an additional association of LGE extent with troponin levels [ 66 , 67 ], which is in line with our observations, while others have not [ 6 , 12 ]. In contrast to these results and our observation, a study by Cramer et al did not show a correlation of cTn with LGE [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, several studies have demonstrated elevated serum levels of cTnI in LGE-positive HCM patients compared to LGE-negative patients [ 6 , 8 , 11 , 17 ]. Besides the mere presence of LGE, some have found an additional association of LGE extent with troponin levels [ 66 , 67 ], which is in line with our observations, while others have not [ 6 , 12 ]. In contrast to these results and our observation, a study by Cramer et al did not show a correlation of cTn with LGE [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…The fact that LGE is often found in hypertrophic segments [ 17 , 68 ] and associated with MWT and greater hypertrophy [ 3 , 6 , 11 , 17 ], similarly to cTn [ 8 , 61 , 67 ], further strengthens the point of a possible association of LGE and cTn. It seems plausible that areas of inadequate hypertrophy exhibit lower perfusion and higher wall stress, with consequently higher rates of cell death and fibrosis and presumably higher cTn release [ 17 ].…”
Section: Discussionmentioning
confidence: 85%